Undifferentiated spondyloarthritis is more frequently seen in women than in men - Sukran Erten; Orhan Küçüksahin; Ali Sahin; Nurdan Cay; Gulay G Ceylan (SpringerOpen, 2015)
Introduction Spondyloarthritis (SpA) are a group of inflammatory rheumatic diseases that share some common clinical and genetic features such as inflammatory back pain, peripheral arthritis, enthesitis, anterior uveitis, sacroiliitis, and HLA-B27 positivity. The aim of the present study was to describe the clinical, radiologic, and genetic features of patients with undifferentiated spondyloarthritis (uSpA) and ankylosing spondylitis (AS). Patients and methods This study included 225 SpA patients (134 uSpA and 91 AS) attending our Rheumatology Outpatient Clinic consecutively. Patients underwent peripheral and axial joint and enthesitis assessment, erythrocyte sedimentation rate or C-reactive protein determination, HLA-B27 tissue typing, radiographic evaluation, and sacroiliac MRI. Results In total, 26 of 91 AS patients and 115 of 134 uSpA patients were women (28.6 vs. 85.8%) and 65 of AS and 19 of uSpA were men (71.4 vs. 14.2%). The time for diagnosis was 15.82 ± 20.7 months for AS patients and 5.91 ± 3.63 months for uSpA patients. Diagnostic delay was 102.46 ± 88.99 (median 83, range 8-377) months for AS and 74.23 ± 60.7 (median 55.5, range 0-238) months for uSpA patients. HLA-B27 positivity was present in 51.6% of AS and 14.9% of uSpA patients. The mean BASDAI level of patients with AS was 6.4 ± 1.1 and that of uSpA patients was 4.8 ± 2.1. Conclusion SpA are frequent diseases and physicians other than rheumatologists should also be aware of them. uSpA is more frequent in women than men. Early diagnosis of SpA is important because early treatment with new biological therapies may lead to much better Results than applying them in the advanced stages.